The Evolution of Money Laundering Enforcement in the Cryptocurrency Age - Kadek Januarsa Adi Sudharma; Anak Agung Alit Satya Prananda, S.H. (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This research examines the regulations and law enforcement efforts concerning the use of cryptocurrency as a money laundering tool in both Indonesia and the United States. Using normative legal research methods and a comparative approach, the study compares the legal frameworks of the two countries. In the United States, agencies such as FinCEN, IRS, and SEC play a critical role in enforcing laws against the use of cryptocurrencies for money laundering, with comprehensive laws and sophisticated enforcement mechanisms. Meanwhile, Indonesia relies on BAPPEBTI to oversee and regulate cryptocurrency activities. Although Indonesia’s legal framework may not be as extensive as the United States', the country has taken significant steps, such as adopting the "Travel Rule" to monitor cryptocurrency transactions. However, both countries face a common challenge: the anonymity offered by cryptocurrencies, which complicates investigations into money laundering. To address this challenge, both countries require more detailed regulations and enhanced international cooperation to effectively combat the misuse of cryptocurrencies for money laundering. The research suggests that strengthening legal measures and improving global collaboration are essential to mitigate the risks associated with cryptocurrency-based financial crimes.